2012
DOI: 10.1021/jz300141n
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diffusion of Chain Molecules in the Metal–Organic Framework IRMOF-1: Simulation and Experiment

Abstract: Metal-organic frameworks (MOFs) possess characteristics, such as tunable pore size and chemical functionality, that make them attractive candidates for separations, catalysis, gas storage, and sensing applications. The rate of diffusion of guest molecules in the pores is an important property for all of these potential applications. In this work, the self-diffusion of hydrocarbons in IRMOF-1 was studied as a function of chain length with a combination of molecular dynamics simulations and pulsed field gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
58
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 26 publications
8
58
1
Order By: Relevance
“…In contrast, the self-coefficient for n-hexane in this material is similar to the ones previously obtained in other MOFs including Cu-BTC [47] and IRMOF-1 [48] (Table. I While the simulations agree well with the experimental data in terms of magnitude of the diffusivity (Fig.…”
Section: Resultssupporting
confidence: 88%
“…In contrast, the self-coefficient for n-hexane in this material is similar to the ones previously obtained in other MOFs including Cu-BTC [47] and IRMOF-1 [48] (Table. I While the simulations agree well with the experimental data in terms of magnitude of the diffusivity (Fig.…”
Section: Resultssupporting
confidence: 88%
“…One observes a non-monotonous decreasing profile characterized by a maximum at C 4 , previously assigned to the blowgun effect [23], and by a sudden drop above C 9 . This behavior differs significantly from the exponential decrease of D s when the chain length increases, as evidenced in silicalite [51] and in IRMOF-1 [35] by QENS and PFG NMR measurements, respectively. Further, compared with silicalite, the self-diffusion coefficient is about one order of magnitude higher, while it spans the same range of values as in IRMOF-1 which shows similar pore size.…”
Section: Resultscontrasting
confidence: 64%
“…The only contribution reported very recently emanates from Ford et al who combined PFG NMR measurements with MD simulations to explore the D s of n-hexane, ndecane, n-dodecane and n-hexadecane in MOF-5 [35]. In this context, following our previous joint QENS-MD studies on the shortlength linear alkanes [22,23] in MIL-47(V) (MIL stands for the Materials of the Institut Lavoisier), here a further step aims (i) to determine the self-diffusivity for longer n-linear alkanes up to nhexadecane in this MOF-type material at low occupancy and (ii) to further elucidate via a detailed analysis of both QENS spectra and MD trajectories the microscopic diffusion mechanism that can explain the chain length dependence of the self-diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Sarkisov et al (2004) reported the self-diffusivities in MOF-5 (also known as IRMOF-1) of various hydrocarbons including n-C 5 to n-C 7 from molecular dynamics (MD) simulations almost two years before the first experimental studies of diffusion in MOFs (Stallmach et al, 2006). Ford et al (2012) reported a combined simulation and experimental study of hydrocarbon diffusion in IRMOF-1 and found excellent agreement between results from MD and from PFG NMR measurements. The self-diffusion coefficients for this system are of same order of magnitude as those in bulk liquids.…”
mentioning
confidence: 99%